2023
DOI: 10.9734/ijecc/2023/v13i113420
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Performance of Latest Greengram Varieties under Improved production Packages in Thiruppur, Tamil Nadu, India

Kathiravan M.,
Vanitha C.,
Ayyadurai P.
et al.

Abstract: On Farm Testing (OFT) in Mungbean Yellow Mosaic Virus (MYMV) resistant and high yielding greengram varieties was conducted by Krishi Vigyan Kendra, Tamil Nadu Agricultural University, Tirupur in farmers field during kharif 2020. Totally 15 farmers each with one acre were selected in three villages of Pongalur Block in Tirupur district of Tamil Nadu.  Critical input viz., seeds of greengram varieties CO 8 and DGG 1 were distributed to the farmers and the varietal performance were assessed along with the existin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…Cultivation of groundnut variety CO 7 with improved production technology recorded 15 per cent more number of pods per plant and 17 per cent higher pod yield [10]. Kathiravan et al [11] found that in greengram, cultivation of improved varieties resulted in higher productivity which facilitates replacement of local varieties Cost of cultivation for sesame TMV 7 variety and local variety were calculated based on the prevailing market prices, wages and other essential input costs. The cost of production of sesame with improved variety and technologies under the demonstration was Rs.…”
Section: Resultsmentioning
confidence: 99%
“…Cultivation of groundnut variety CO 7 with improved production technology recorded 15 per cent more number of pods per plant and 17 per cent higher pod yield [10]. Kathiravan et al [11] found that in greengram, cultivation of improved varieties resulted in higher productivity which facilitates replacement of local varieties Cost of cultivation for sesame TMV 7 variety and local variety were calculated based on the prevailing market prices, wages and other essential input costs. The cost of production of sesame with improved variety and technologies under the demonstration was Rs.…”
Section: Resultsmentioning
confidence: 99%